2015
DOI: 10.4018/ijissc.2015010101
|View full text |Cite
|
Sign up to set email alerts
|

Using Social Network Analysis to Explore Digital Student Interactions and Business Competency Learning in a Web-based Educational Platform

Abstract: Web 2.0 tools occupy a large part of our lives, and their use in the classroom offers instructors a unique opportunity to gather substantial information about individual and interactive student behaviors. The authors' challenge is understanding the implications of this rich data source for assessing course efficacy and student learning, and applying these insights to further enhance the development of global business competencies. This paper reviews 311 student interactions as reflected in comments exchanged i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…In this study, data was also analyzed with Social Network Analysis (SNA) in Gephi. Examples of SNA in education research include Feldstein and Gower (2015) who analyzed the network of comments exchanged by students in the knowledge-building blog deployed in an undergraduate brand management course. The authors found SNA provided an opportunity to gauge the communicative interactions that take place and to assess the relationship between the students' positions within the network, their communication and collaborative feedback skills, and course outcomes (Feldstein & Gower, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this study, data was also analyzed with Social Network Analysis (SNA) in Gephi. Examples of SNA in education research include Feldstein and Gower (2015) who analyzed the network of comments exchanged by students in the knowledge-building blog deployed in an undergraduate brand management course. The authors found SNA provided an opportunity to gauge the communicative interactions that take place and to assess the relationship between the students' positions within the network, their communication and collaborative feedback skills, and course outcomes (Feldstein & Gower, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Examples of SNA in education research include Feldstein and Gower (2015) who analyzed the network of comments exchanged by students in the knowledge-building blog deployed in an undergraduate brand management course. The authors found SNA provided an opportunity to gauge the communicative interactions that take place and to assess the relationship between the students' positions within the network, their communication and collaborative feedback skills, and course outcomes (Feldstein & Gower, 2015). In addition to data visualization and SNA, multiple linear regression was used in this study to determine whether students' course grades could be predicted by their engagement using Yellowdig in the classes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Network science was proposed as a method to better comprehend the contribution of networking and interactivity among health professionals in professional communities regarding their learning and application of new practices over time. Feldstein et al [4] reviewed interactions of 311 students reflected in the comments in a digital social learning community and adopted social network analysis to discuss the possibility of applying these interactions to evaluate students' critical thinking, communication, and collaborative feedback skills. The authors summed up the implications and recommendations for instructors who hope to apply Web 2.0 platforms and data to strengthen their understanding of students and class digital interactions and adopt the information to enhance courses.…”
Section: State Of Artmentioning
confidence: 99%